JOB SATISFACTION EMPLOYEES HOSPITAL - Siti Mariam (Universitas Trisakti, 2019)
The design of this research applies descriptive research and correlation research with etchical leadership, organizational commitment and job satisfaction as dependent variables. The primary data is taken from respondents which are employees of the Private hospital at Jakarta Barat. As conclusion, the are has influence positive and significance of etchical leadership toward organizational commitment, the are has influence positive and significance of etchical leadership toward job satisfaction, the are has influence positive and significance of organizational commitment toward job satisfaction, the are has influence positive and significance of etchical leadership toward job satisfaction with organizational commitment as mediating variable.